(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aimed to determine the marketing strategies used by the Grade 12 online seller and help the businesses with the help of proposed intervention and remediation. Results showed that customer service, brand recognition, and consumer behavior have their own advantages and disadvantages. With the help of proposed interventions like social media or remediation of the disadvantages, the challenges to the businesses are lessened.